Pengaruh Praktik Kerja Industri, Lingkungan Keluarga, Bimbingan Karier dan Motivasi Kerja terhadap Kesiapan Kerja - Apriliana Khulasatul Mutoharoh; Wisudani Rahmaningtyas (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study was to determine the effect of industrial work practices, family environment, career guidance and work motivation on student work readiness. The population of this study was 145 studentsof of class XI administrasi department at SMK Batik 1 Kebumen. The research method with causality design. Total sample was obtained 106 by proportional random sample technique. Data collection techniques used were questionare, interview and documentation. Data analysis method used the classical assumption test of multiple linear regression analysis and hypothesis testing. Industrial work practices has an effect on work readiness 13,84%, family environment influences work readiness 12,11%, while career guidance and work motivation do not affect work readiness.